Software-Based Postoperative Communication With Patients Undergoing Spine Surgery. Issue 1 (February 2019) - Goz, Vadim; Anthony, Christopher; Pugely, Andrew; Lawrence, Brandon; Spina, Nicholas; Brodke, Darrel; Spiker, William Ryan
Study Design: Observational study. Objectives: Perioperative patient anxiety is a major concern in orthopedic surgery. Mobile messaging applications have been used in a number of healthcare settings. The goal of this project is to develop a novel mobile messaging application aimed at decreasing perioperative patient anxiety in spine surgery patients. Methods: Postoperative recovery journals were collected from patients undergoing spine surgery. Journals were used as a framework to develop a software-messaging library. A subsequent cohort of patients received daily text messages with educational material regarding their recovery for 14 days after discharge from their operative admission. Patients ranked the usefulness of the survey on day 14; further feedback was obtained via interviews. Results: Nineteen postoperative recovery journals were collected and analyzed. Content regarding postoperative recovery was compiled. The pilot group consisted of 21 patients. Average rating of the application on a 1 to 5 scale with 5 being "very useful" was 4.57. Of the 12 patients available for postoperative interviews, 11 felt the content of the messages was relevant. Nine of 12 patients felt the application made it less likely for them to call clinic. Conclusions: The study presents a unique mobile phone messaging tool to offer patients support in the 2 weeks following spine surgery. The tool was felt to be useful by nearly all patients, had a high degree of patient engagement, and made the majority of patients less likely to call clinic.